Numerical simulation research on the micro failure mechanism of sandstone under freeze-thaw cycles - Tao, Li; Peng, Wu; Shanchao, Hu; Boyuan, Wu; Zhanqing, Chen (Frontiers in Earth Science, 2025)
The process of micro crack formation in sandstone subjected to freeze-thaw cycles is pivotal for strip mine in cold regions. A discrete element numerical model considering the variation of frost heave force and water saturation during the freeze-thaw cycles is established by PFC3D in this paper. The results indicate that: (1) During freeze-thaw cycles, the development of cracks can be divided into three stages: stable, growth and explosive stage. The crack quantity in the stable and growth stage increases exponentially, while the quantity of cracks in the explosive stage increases linearly quickly. (2) Repeated freeze-thaws cause progressive damage to rocks from surface to interior. As the times of freeze-thaw increase, cracks gradually develop, and their distribution becomes more uniform on different angles. (3) Sandstone that have undergone freeze-thaw cycles is more prone to tensile failure, and the distribution of cracks becomes even more complex. These research findings provide a more accurate understanding of micro-fracture mechanisms in rocks in the freeze-thaw condition.